Meluruskan Isu Tentang “Ada Keselamatan di Luar Yesus” Sebagai Apologetika terhadap Finalitas Yesus - Siringo Ringo, Lumayan; Sunarno, Sunarno (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2024)
The saving work of Jesus Christ on the cross is a central pillar in Christian teaching, which affirms that human salvation can only be obtained through faith in Him.  This article aims to  to straighten out the understanding of both Christians and non-Christians about the existence of salvation other than Christ.   This is not new but has been around for a long time. This issue is increasingly packaged in such a way by pluralists who are actually the product of rationalism. This understanding popularizes inclusive safety is no longer exclusive. So the researcher can say that this understanding is not in accordance with the truth of the Bible and even contradicts the truth of God's words. The conclusion of this article is that salvation in Christ is exclusive and final, it cannot be changed by man, because exclusive salvation is a great gift for every believer. This research uses a qualitative approach with content analysis where it is firmly stated that there is no salvation outside of Jesus, because salvation is only in the name of Jesus Christ and it is final.